Spatiotemporal variation in the interactions between rural tourism and rural settlements in Shanxi and Shaanxi Provinces, China - Xiaoqin Geng; Ruiqin Ma; Li Liu; Yixiong Wu (PLoS ONE, 2025)
Rural revitalization requires the coordinated development of rural tourism (RT) and rural environments for human settlements. The Chinese provinces of Shanxi and Shaanxi face significant interregional differences as they seek to improve their rural human settlements. This study constructed an index system to evaluate the relationship between RT and rural settlements using the entropy method. The level of coordination between RT and the development of rural settlements in the two provinces during the period 2013–2022 was then analyzed based on the extent of their interaction (i.e., their coupling coordination degree). Key drivers of this coordination were identified using the geographic detector method. The results indicated that the coordination between RT and rural settlements has generally improved in both provinces, but regional disparities remain significant. Central cities are the most developed, while resource-dependent cities and remote areas lag. Critical drivers of coordinated development included economic development, resource attractiveness, and service support. Policy recommendations to promote the balanced development of RT and rural settlements include strengthening the protection of the environment, improving infrastructure, fostering industrial integration, and cultivating human resources.